Hadith #4668 - Sunan Abi Dawud - Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Abdullah ibn Ja'far; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isma'il bin Abi Hkym إسماعيل بن أبي حكيم القرشي; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Abi Dawud)
Do not distinguish between the Prophets.
Grade: Sahih